2018
DOI: 10.1085/jgp.201812086
|View full text |Cite
|
Sign up to set email alerts
|

Determining the molecular basis of voltage sensitivity in membrane proteins

Abstract: Voltage-sensitive membrane proteins are united by their ability to transform changes in membrane potential into mechanical work. They are responsible for a spectrum of physiological processes in living organisms, including electrical signaling and cell-cycle progression. Although the mechanism of voltage-sensing has been well characterized for some membrane proteins, including voltage-gated ion channels, even the location of the voltage-sensing elements remains unknown for others. Moreover, the detection of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 120 publications
(390 reference statements)
1
16
0
Order By: Relevance
“…Inside a VSD, they interact with negative counterparts coming from the remaining S1–S3 segments through salt bridges. Upon electric-field application, the S4 residues move along its direction, causing the disruption of existing salt bridges and formation of new ones ( 58 , 59 , 60 ). In our simulations, application of the electric field modified the salt-bridge connections within the investigated VSD: some existing salt bridges were broken, and new salt bridges were formed.…”
Section: Resultsmentioning
confidence: 99%
“…Inside a VSD, they interact with negative counterparts coming from the remaining S1–S3 segments through salt bridges. Upon electric-field application, the S4 residues move along its direction, causing the disruption of existing salt bridges and formation of new ones ( 58 , 59 , 60 ). In our simulations, application of the electric field modified the salt-bridge connections within the investigated VSD: some existing salt bridges were broken, and new salt bridges were formed.…”
Section: Resultsmentioning
confidence: 99%
“…9, video). A recent computational analysis aimed at 550 predicting intrinsic or extrinsic elements of a protein that could respond to changes in the local 551 electric field indicated that either Glu gate or a Cl -ion trapped in the pore could participate in 552 voltage sensing in CLC--1 (Kasimova et al, 2018). According to our simulations, Glu gate moved 553 outwardly ∼7 Å from its original closed position but remained interacting with Lys212 until it 554 was protonated.…”
Section: Fig 9 Schematic Representation Of the Electro--steric Activmentioning
confidence: 75%
“…Inside a VSD they interact with negative counterparts coming from the remaining S1-S3 segments through salt bridges. Upon electric field application, the S4 residues move along its direction causing the disruption of existing salt bridges and formation of new ones (56)(57)(58). In our simulations, application of the electric field modified the salt-bridge connections within the investigated VSD: some existing salt bridges were broken, and new salt bridges were formed.…”
Section: Salt Bridges Reorganization In Vsdsmentioning
confidence: 78%